Application of nanofluids in gas turbine and intercoolers - a comprehensive review - Almertejy, Ali; Rashid, Muhammad M.; Ali, Naser; Almurtaji, Salah (MDPI, 2022)
Today, the optimal use of non-renewable energy sources, reducing pollution, and increasing the efficiency of power-generating cycles are of particular importance. There are several ways to increase the efficiency of gas turbines; one that has recently attracted attention is to use an intercooler. However, the efficiency of the heat exchanger used in intercoolers depends on the type of heat exchanger, the characteristics of the operating fluid and the thermal boundary layers, and the pump speed. Improving the thermophysical properties of the working fluid is a passive method of increasing heat transfer, which has attracted the attention of those researching engineering applications. The current review addresses the latest methods of improving gas turbine efficiency using nanofluids and includes experimental and numerical studies. First, the general principles governing turbines are described, then the commonly used types of heat exchangers are introduced. Finally, studies on the use of nanofluids in heat exchangers are reviewed. The technology of producing nanoparticles that can be used in heat exchangers is also discussed. This review article can provide the reader with comprehensive information on making nanofluids and using them in heat exchangers used as intercoolers.
Keywords: gas turbine; intercooler; heat transfer; heat exchanger; thermal efficiency; nanofluid